BN's pledges 'realistic, achievable' - Najib, Najmuddin (New Straits Times, 2013)
A DAY after the launch of the Barisan Nasional election manifesto by Prime Minister Datuk Seri Najib Razak, its pledges and underlying theme continue to draw praise from all quarters.